Leasing in Emerging Markets : A Potent Instrument for Financing Small Business? - Barger, Teresa; Carter, Laurence; Kuczynski, Irving (World Bank, Washington, DC, 2012)
IFC has built up a hefty portfolio of debt and equity investments in leasing companies in emerging markets. Based on IFC's experience, the authors argue that leasing is an effective instrument for financing small firms' investments in equipment --especially in countries with weak collateral laws or mostly new businesses that lack historical financial statements.